2020
DOI: 10.1177/1535370220908041
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA KCNQ1OT1 attenuates sepsis-induced myocardial injury via regulating miR-192-5p/XIAP axis

Abstract: Myocardial dysfunction is a prime cause of death in sepsis. This study is to delve into the function of lncRNA KCNQ1OT1 in myocardial injury induced by sepsis. Sepsis-induced myocardial injury model in rat was initiated by intraperitoneally injecting of LPS (10 mg/kg) in vivo, and cardiomyocyte H9c2 was treated with LPS to mimic sepsis in vitro. KCNQ1OT1 and miR-192-5p expressions were detected by qRT-PCR. The cell viability was probed with CCK-8 experiment and the apoptosis of the cardiomyocytes was tested us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 39 publications
0
45
0
Order By: Relevance
“…Due to the nature delivery systems of exosomes between cells, some therapeutic miRNAs can be appropriately packaged in exosomes to target specific recipient cells. Intriguingly, increasing reports indicate that the expression levels of miRNAs are regulated by long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) ( Cai et al, 2019 ; Liu et al, 2019 ; Sun et al, 2020 ). Noteworthily, cytoplasmic lncRNAs or circRNAs frequently possess potential sites for binding to certain miRNAs, and can repress miRNA function by acting as miRNA sponges in tumor development ( Shi et al, 2013 ; Kulcheski et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the nature delivery systems of exosomes between cells, some therapeutic miRNAs can be appropriately packaged in exosomes to target specific recipient cells. Intriguingly, increasing reports indicate that the expression levels of miRNAs are regulated by long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) ( Cai et al, 2019 ; Liu et al, 2019 ; Sun et al, 2020 ). Noteworthily, cytoplasmic lncRNAs or circRNAs frequently possess potential sites for binding to certain miRNAs, and can repress miRNA function by acting as miRNA sponges in tumor development ( Shi et al, 2013 ; Kulcheski et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this pathway, down-regulation of CYTOR or up-regulation of miR-24 appeared to worsen sepsis-induced myocardial injury via activation of apoptosis. Sun et al demonstrated the role played by lncRNA KCNQ1OT1 in the regulation of miR-192-5p in myocardium damage by sepsis [ 74 ]. KCNQ1OT1 downregulated miR.192-5p, which in turn inhibits the translation of XIAP, improving myocardiocyte viability and contrasting apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the aforementioned studies demonstrated that PTEN is targeted by miRNAs in sepsis-induced cardiac damage [ 53 , 59 , 60 ]. A further complication in understanding the role of miRNAs in septic myocardial injury is represented by lncRNAs, as evidenced by some research studies mentioned above [ 45 , 73 , 74 ]. Since they have the property of inhibiting miRNAs, they seem to play a crucial role in the tangled forest of those interconnected signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations